INOVASI PELAYANAN PUBLIK IZIN MENDIRIKAN BANGUNAN DI KOTA BUKITTINGGI - Fiyolla Junita Sari; Nellis Mardhiah (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2022)
The Building Permit is a form of permit granted by the One Stop Integrated Investment Agency for Industry and Manpower in the City of Bukittinggi from various kinds of permits granted. In this study, to see the Public Service Innovation of Building Permits in the City of Bukittinggi. This study applies a qualitative method. The object of this research is the Front Office DPMTSPPTK which is involved in providing services, Sector B staff who are involved in obtaining building permits. The results of the data obtained by conducting in-depth observations or examinations, interviews or questions and answers, data, and documentation. Based on the results of the study, various obstacles were found in the process of implementing public service innovations such as the use of SIMBG carried out by the Bukittinggi City DPMTSPPTK. As the focus of the research, which describes more public service innovations in the Bukittinggi City DPMTSPPTK. There are 5 innovation indicators proposed by Rogers in the Pangestu, namely Relative Advantage, Compatibility, Triability, and Observability.At the end of the study, it can be concluded that DPMPTSPTK has implemented innovations in public services, al though there are still things that need to be improved and improved.